THE ROLE OF HEALTH POLYTECHNIC OF PALANGKA RAYA AS A LEADING CENTER FOR ADOLESCENT HEALTH IN CENTRAL KALIMANTAN - Dhini Dhini (Proceedings of the International Conference on Applied Science and Health, 2019)
-